An Empirical Study of Leadership Styles and Employee Productivity: Evidence from Diageo, UK - Datta, Rajib; Jahan, Dilshad (Archives of Business Research, 2025)
Leadership plays a pivotal role in shaping organizational performance by influencing employee motivation, satisfaction, and productivity. Although leadership has been studied extensively, there is a noticeable research gap concerning its impact within the alcoholic beverages industry, and more specifically, a scarcity of evidence from Diageo, UK ((United Kingdom). This study explores how different leadership styles - transformational, transactional, laissez-faire, servant, and authentic—affect employee productivity in this context. A mixed-methods design integrating quantitative surveys and qualitative interviews is proposed to examine leadership practices and their outcomes. The study aims to contribute to theoretical understanding and offer practical recommendations to enhance employee productivity in Diageo and similar organizations.